Severe Cutaneous adverse reactions in a local hospital setting in Bangladesh: a 5-year retrospective study - Hoque, Mohammad Enamul; Khan, Md. Abdul Latif; Khan, Md. Shirajul Islam; Hoque, Md. Mominul; Hossain, Nazmul (Journal of Pakistan Association of Dermatologists, 2023)
Background: Cutaneous Adverse Drug Reactions (CADR) are frequent adverse drug reactions that can present in various ways and range in severity. The most typical drug allergy symptom is skin manifestation, underscoring how crucial it is to identify the offending medication and stop using itâ€”doing so could even save your lifeâ€”in some cases. Aim: This study aimed to determine the frequency of severe and deadly cutaneous adverse drug reactions (SCAR) in hospitalized Bangladeshi patients and calculate the prevalence of severe and deadly cutaneous adverse drug reactions (SCAR) in hospital patients. Methods: Inpatient records from the Department of Dermatology and Venereology, Combined Military Hospital, Dhaka, were used to gather data retroactively throughout the time frame of January 2012 to December 2016. Age, gender of the patients, implicated drugs, observed drug reactions, course of treatment, and results were some variables we examined (mortality and morbidity). Results: Clinical evaluation of the study participants revealed that 46% of cases were SJS, 29% were TEN, 16% were DRESS, and 10% were AGEP. The age range of 31 to 50 years saw the highest incidence (46%) of cases. Drug classes that contain anticonvulsants may have the highest incidence of SCADRs. Phenytoin caused 16% of patients’ SCADRs, followed by carbamazepine in 22% of instances and phenobarbital in 14% of cases. Conclusion: SCADRs have been a serious issue in healthcare for decades. The majority of SCADR is caused by medications that doctors give. SCADRs were more frequently observed with anticonvulsants from the carbamazepine and phenytoin categories. Continuous monitoring of SCADRs is necessary to develop preventive measures.